Novel Optimization Algorithm Inspired by Camel Traveling Behavior - Ibrahim, Mohammed Khalid; Ali, Ramzy Salim (Iraqi Journal for Electrical and Electronic Engineering, 2017)
This article presents a novel optimization algorithm inspired by camel traveling behavior that called Camel algorithm (CA). Camel is one of the extraordinary animals with many distinguish characters that allow it to withstand the severer desert environment. The Camel algorithm used to find the optimal solution for several different benchmark test functions. The results of CA and the results of GA and PSO algorithms are experimentally compared. The results indicate that the promising search ability of camel algorithm is useful, produce good results and outperform the others for different test functions.